Four Legs of the Table in Increasing Academic Success in Students; Nutrition, Sleep, Physical Activity and Social Life - MUSLU, Mücahit (Burdur Mehmet Akif Ersoy University, 2023)
Students must be physically, psychologically and socially good for their academic success. This is closely related to their lifestyle. Students' lifestyles are affected by many factors such as personal characteristics, health status, environment, family, economic situation, culture and policies. Lifestyle factors such as nutrition, physical activity, sleep quality and social relationships have significant effects on academic achievement. For high academic success, it is recommended that students eat an adequate and balanced diet, avoid products with low nutritional value, do not consume caffeine more than the recommended amount, do not take caffeine in the afternoon, do not prefer energy drinks, and avoid unnecessary supplements. All students are required to engage in moderate-intensity regular physical activity appropriate to their individual circumstances. In order to increase sleep quality, it is recommended to sleep in the appropriate clothing and physical conditions early in the recommended time. For psychosocial well-being, social relations should be kept high, effective communication with peers, teachers and families, and out-of-school activities should be supported. In addition, necessary physical conditions should be provided to increase student success, development of inclusive education policies, legislation and supervision should be provided.
Keywords: Sağlığın Geliştirilmesi; öğrenciler; akademik başarı; beslenme; uyku; sağlık; Health Care Administration; Sağlık Kurumları Yönetimi; Health Promotion; students; academic success; nutrition; sleep; health; 2. Zero hunger; 4. Education; 11. Sustainability; 16. Peace & justice; 10. No inequality; 7. Clean energy; 3. Good health